Tiras de carga e supercondutividade - Tunes, Thiago Miranda (2009)
Charge stripes are believed to be a possible mechanism driving the superconducting transition in the cuprates. In this work we consider a "striped" repulsive Hubbard model on a square lattice, in which anisotropic hopping (i.e., ty = r tx, r < 1) favours electronic motion along one direction. Previous mean- eld ananlyses of the model found that for a xed electronic density away from half lling the superconducting critical temperature could be enhanced up to three orders of magnitude; the hopping ratios considered there were r = 0.1, 0.01 and 0.001. By means of Quantum Monte Carlo (QMC) simulations, we investigate several physical properties of the model, such as the magnetic structure factor at q = (π, π), the structure factor for three di erent pairing states (s-wave, d-wave, and extended s-wave); we also examine transport properties, such as the temperature behaviour of both the conductivity (along x and y directions) and the density of states at the Fermi level. As a rst approach to the problem, we have only considered the case of a half- lled band; in this way, there are no "minus-sign problems" in QMC. We have calculated the above quantities for even lattice sizes ranging from L = 8 to 16, in order to perform reliable nite-size scaling analyses to extract the behaviour of the staggered magnetization and of the superconducting gap (both in the ground state, through the Huse scaling) with anisotropy; we have also examined the isotropic case, r = 1, for comparison. We have found that the antiferromagnetic ground state, present in the isotropic case (r = 1), is no longer the dominant one for the anisotropies considered here, r = 0.1, 0.01 and 0.001; the zero-temperature gap vanishes in all cases, similarly to the isotropic case. While for r = 1 the conductivity is isotropic, as it should, we have found that anisotropic hopping decreases the conductivity in the favoured direction (x) as well; the density of states at the Fermi level follows a similar pattern.